Praktik Money Politik dalam Pemilihan Legislatif 2024 Terhadap Demokrasi Lokal Masyarakat Kabupaten Alor - Winda Riandar Koso; Akhmad Syafruddin; Frans B. R. Humau (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to examine the practice of money politics that occurred in the 2024 Legislative Election in Alor Regency and its impact on the quality of democracy in the region. Money politics is a highly relevant issue because it has the potential to undermine the basic principles of democracy, reduce electoral integrity, and create inequities in political representation. This practice generally involves giving money or goods to voters with the aim of influencing their political choices, which of course reduces the quality of public political participation. A qualitative approach was used in this study, with data collection techniques including in-depth interviews with various parties involved in the election process, direct field observations, and a review of documents relevant to the elections in Alor Regency. This technique allows for more in-depth data collection and provides a better understanding of how money politics occurs at the local level. The results show that the practice of money politics still frequently occurs in the lead-up to election day, both in the form of giving cash and goods to voters. This phenomenon indicates a decline in the quality of public political participation, where political choices are more influenced by material rewards than by considering the competence of legislative candidates. This indicates a disorientation in the democratic process, where voters focus more on immediate gains than on the capacity and integrity of candidates. The impact of this money politics practice is significant for local democracy. The decline in public trust in the political process exacerbates the dependency between voters and political elites, which in turn leads to inequality in political access and representation. Therefore, this study recommends strengthening political education for the public and stricter law enforcement against perpetrators of money politics to improve the quality of democracy in Alor Regency.